Shade tolerance in wheat is related to photosynthetic limitation and morphological and physiological acclimations - Li, Yong; Zhao, Jiarong; Ma, Hongliang; Pu, Lixia; Zhang, Jiarui; Huang, Xiulan; Yang, Hongkun; Fan, Gaoqiong (Frontiers in Plant Science, 2024)
Low solar irradiance reaching the canopy due to fog and heavy haze is a significant yield-limiting factor worldwide. However, how plants adapt to shade stress and the mechanisms underlying the reduction in leaf photosynthetic capacity and grain yield remain unclear. In this study (conducted during 2018–2021), we investigated the impact of light deprivation (60%) at the pre-anthesis and post-anthesis stages on leaf carboxylation efficiency, source-to-sink relationships, sucrose metabolism, and grain yield of wheat cultivars with contrasting shade tolerance. Shade stress decreased stomatal conductance, stomatal limitation value, intrinsic water use efficiency, rubisco activity, and carboxylation efficiency of flag leaves during grain-filling, whereas intercellular CO2 concentration increased. These findings indicate that non-stomatal limitation reduces the net photosynthesis rate in a weak-light environment. Shade-tolerant cultivars (MM-51 and CM-39) adapted to low-light conditions via a higher leaf area of flag leaves, light interception rate, and chlorophyll a and b contents; this increased non-structural carbohydrates and sucrose contents in developing grains, ultimately decreasing yield loss by shade stress. Pre-anthesis shading resulted in a greater yield loss than post-anthesis shading because of decreased plant biomass, grain number per spike and 1,000-kernel weight. This study indicates that Rubisco-mediated non-stomatal limitation reduces PN and sucrose content in plants exposed to low-light stress, contributing to decreased grain yield. Our study provides information on the mechanism underlying shade stress tolerance, which will help design future strategies for reducing yield loss in the context of global dimming.